Mental health disorders in English newspapers of India: A retrospective study. (May 2023) - Arneaud, Gervan J; Kar, Anindya; Majumder, Sunrit; Molodynski, Andrew; Lovett, Kate; Kar, Satyabrata
Background: In recent years there has been significant coverage of mental health in Indian newspapers; the media can play a significant role in perpetuating as well as reducing stigma towards people with mental illness. This paper analyses the content, context and type of newspaper coverage of various mental health disorders in English language newspapers in India between 2016 and 2021. Methods: A detailed analysis was performed on a sample of articles about mental illness in a range of English language Indian newspapers. Results: Depression was the most prevalent topic amongst the articles followed by anxiety, schizophrenia and bipolar disorder. Our study describes a wide range of use of mental health disorders in various newspapers. All diagnoses were generally described in a criminal context like homicide, sexual assault and other crimes. Over time newspaper coverage of mental illness has become less stigmatising. Further exploration of non-English medium newspapers is required to fully understand the extent of the role of print media in perpetuating unhelpful stereotypes of people with mental illness in India.